2016
DOI: 10.5152/tao.2016.1556
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Acoustic Reflex and Reflex Decay Tests in Geriatric Group

Abstract: Objective: To determine average acoustic reflex thresholds in geriatric groups by assessing ipsilateral and contralateral acoustic reflex and reflex decay tests. Methods:A total of 25 elders between ages 65-84 years (74.3±5.4) and 25 individuals between ages 18-45 years (30.4±4.2) were recruited for the study. After ear, nose, and throat examination, ipsilateral and contralateral acoustic reflex thresholds at 500, 1000, 2000, and 4000 Hertz (Hz) were determined and a reflex decay test at contralateral 500 Hz w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…According to the results of ipsilateral and contralateral acoustic reflex of both ears, information about lesion locations and their effects on hearing can be obtained. [26] In this study, no statistically significant difference was observed between keratoconus and healthy subjects in acoustic ref lex evaluation. This shows that no pathological changes have been observed in the anatomical structures of the acoustic reflex pathway.…”
Section: Discussioncontrasting
confidence: 49%
“…According to the results of ipsilateral and contralateral acoustic reflex of both ears, information about lesion locations and their effects on hearing can be obtained. [26] In this study, no statistically significant difference was observed between keratoconus and healthy subjects in acoustic ref lex evaluation. This shows that no pathological changes have been observed in the anatomical structures of the acoustic reflex pathway.…”
Section: Discussioncontrasting
confidence: 49%
“…Moreover, MEMR growth has been observed to decrease as a function of age (Thompson et al, 1980 ). In contrast, Unsal et al ( 2016 ) found no differences in either the MEMR thresholds (obtained by the standard clinical probe tone approach) using 4 kHz tonal elicitors, or the MEMR decay, between older and younger adults. The correlation between MEMR thresholds/growth functions and aging in the above studies could be at least partially explained by age-related declines in central auditory neural pathways (Ouda et al, 2015 ), which need to be accounted for in the investigation of age-related CS using MEMR measures.…”
Section: Objective Proxy Measures Of Cochlear Synaptopathymentioning
confidence: 91%
“…A study was done to assess the ART and RDT in the geriatric group by Ünsal et al who concluded that although some changes were observed due to age, middle ear and stapedius work normally in geriatric category as no significant difference was found between geriatric and non-geriatric categories in ipsilateral and contralateral AR parameters and RDT [ 13 ]. Virtaniemi et al concluded that decreased ARAs and prolonged ARLs in subjects with insulin-dependent diabetes mellitus (IDDM) were more probably attributed to the rigid middle ear structure than brainstem alterations [ 14 ].…”
Section: Discussionmentioning
confidence: 99%